PERAN GEREJA DALAM MEMUTUS MATA RANTAI KEKERASAN SEKSUAL TERHADAP ANAK - Grecetinovitria Butar-butar; Ibelala Gea; Herdiana Boru Hombing (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
Sexual violence against children requires preventive efforts accompanied by serious and sustained measures to break the chain of sexual violence against children. The purpose of this study is to determine the role, efforts, and solutions that can be implemented by the church in breaking the chain of sexual violence against children. In analyzing this issue, the research method used is qualitative research and a descriptive approach. Based on the research, the results show that efforts to break the chain of sexual violence can be carried out through the church's work in the areas of Koinonia, Marturia, and Diakonia. Solutions and efforts that can be made by the church can begin with awareness of the ecosystem of sexual violence against children, followed by concrete action. The church needs to voice the urgency of sexual crimes and appeal to the congregation through sermons to increase awareness and supervision of children, provide faith guidance for all categorical groups, and provide assistance to victims.